PRINTED HYPERMEDIA-BASED PBL INSTRUCTIONAL MATERIALS FOR THE MOTORCYCLE IGNITION SYSTEM: A SYSTEMATIC REVIEW - Deomesta Oscar Daeli; Eveline Siregar; Cecep Kustandi (El Midad, 2026)
Learning the motorcycle ignition system in Vocational High Schools requires instructional materials that can visualize electrical processes, intercomponent relationships, and contextual fault-diagnosis procedures. This study formulates a conceptual framework for developing printed hypermedia-based Problem-Based Learning (PBL) instructional materials for the motorcycle ignition system, guided by three research questions: the characteristics of relevant hypermedia materials (RQ1), the contribution of PBL to problem solving and critical thinking (RQ2), and the conceptual basis for integrating printed materials, QR-code-based hypermedia, and PBL (RQ3). A Systematic Literature Review was conducted following the PRISMA flow; literature was retrieved from the Sinta and Scopus databases for 2021–2025. Of 487 records identified, 30 met the inclusion criteria and were analyzed through thematic synthesis. The findings show that hypermedia, multimedia, augmented reality, and virtual laboratories support the visualization of abstract electrical processes (RQ1); PBL builds diagnostic reasoning and problem solving, raising competency mastery in automotive contexts (RQ2); and the print–hypermedia–PBL integration is conceptually feasible but not yet tested, as only two studies address the ignition system and only four support printed hypermedia materials (RQ3). The synthesis is formulated into a conceptual framework as a basis for further development research through expert validation, practicality testing, and effectiveness testing.